Desenvolvimento de reatores eletroquímicos para o tratamento de água produzida de petróleo. - Santos, Amaro Carlos dos (2006)
The production of oil in Brazil is increasing to each year. As result a increasing volume of production water is generated as part of the process itself of formation of the deposits, many times in bigger ratios that the oil itself. The produced water owns a great diversity of contaminants, what ally to its high volume, brings serious problems at the moment of giving a final disposal to it. Some solutions had been attempted; on account of the more restrictive laws each day of the ambient agencies, but still in palliative way. The present work considers evaluating eletrodics materials and experimental conditions adjusted to be used in reactors, propitiating the electrochemical treatment of this residue. As anodes Ânodos Dimensionalmente Estáveis (ADE) commercial had been used, with nominal composition of Ti/Ru0,34Ti0,66O2. As cathodes the ADE, 316 steel and graphite had been evaluated. Amongst the cathodic materials studied the steel it presented performance better, as much with regard to efficiency of the process how much in the reduction of the cathodic incrustation. In the studies in batelada, was verified that the dilution of the solution and the current density influence significantly in the efficiency of the oxidation process. The increase of the dilution increases greatly the efficiency of the process. Already the speed of reduction of the DQO increases with the current density, however, the increase is not linear indicating that the process is controlled for diffusion. The efficiency of the electrochemical process in the reduction of the DQO of the sample was associated the three factors:a) the direct oxidation of the organic residue on the electrode; b) removal of the powdered material for the eletrogenerated gases (eletroflotation); c) indirect oxidation through reactive intermediate species. In the case of the reactor, it could be noticed that, the control of the outflow and the current density, as well as of the height of the flotant column influence in the efficiency of the treatment of the effluent, one beyond minimizing the incrustation on the cathodes. In the optimized conditions: outflow 800mLh-1, current density of 50mAcm-2 and flotant column of 10cm got it considerable reduction of the DQO and the TOG, proving the possibility of the application of the electrochemical technology in the treatment of the produced water of oil.